Independent role of two novel abdominal fat indicators in chronic diarrhoea - Chen, Shiming; Zhang, Jingxia; Niu, Yingxue; Li, Yifang (Frontiers in Medicine, 2025)
BackgroundStudies have confirmed that obesity is an antecedent of chronic diarrhoea, and new evidence suggests that visceral fat accumulation may play a more critical role than total body fat in intestinal dysfunction and the development of chronic diarrhoea. Traditional body mass index (BMI) does not accurately reflect fat distribution, limiting the depth of relevant research. Body shape index (ABSI) and body rounding index (BRI), as emerging measurements that more accurately assess abdominal and visceral adiposity, have shown superior predictive value to BMI in cardiovascular and metabolic diseases. However, the use of these metrics in the prediction of chronic diarrhoea has not been explored. This study is the first to investigate the relationship between ABSI and BRI and chronic diarrhoea, aiming to provide a new clinical tool for risk assessment of obesity-related diarrhoea.MethodsThis study used data from the Bowel Health Questionnaire (BHQ) of the U.S. National Health Examination Survey (NHANES) database (2005–2010), and chronic diarrhoea was defined as “chronic diarrhoea” by the Bristol Stool Scale (BSFS) types 6 andI7(4). Weighted logistic regression and trend analyses were performed to examine the association between ABSI/BRI and chronic diarrhoea. Flexible restricted cubic spline (RCS) models showed dynamic associations. Stratified analyses examined associations between age, gender, race, and clinical characteristics (e.g., cardiovascular disease, diabetes, hypertension). Receiver operating characteristic (ROC) curves assessed the predictive performance of ABSI/BRI for risk of chronic diarrhoea.ResultsMultivariate regression models with time-trend analyses indicated a dose–response relationship between higher BRI percentiles and the incidence of chronic diarrhoea. 13% per unit increase in BRI (OR = 1.13, 95% CI = 1.08–1.19, p < 0.001). Similarly, there was a 35% increase in risk for each 0.01 unit increase in ABSI (OR = 1.35, 95% CI = 1.01–1.80, p = 0.045), suggesting that those with higher ABSI were at higher risk. Subgroup analyses showed no significant interaction effect between BRI and chronic diarrhoea across age, sex, race, cardiovascular disease, diabetes, and hypertension (p > 0.050). The ROC confirmed the nonlinear association between ABSI/BRI and chronic diarrhoea.ConclusionThe objective of this study was to investigate the association between two novel abdominal fat indicators (ABSI and BRI) and chronic diarrhoea using nationally representative NHANES data (2005–2010). For the first time, we have identified ABSI and BRI as potentially useful clinical predictors of chronic diarrhoea.